ORGANOLOGICAL REVIEW OF ARI GUNADI'S CLASSIC GUITAR BRACING IN RANGKASBITUNG - Furqon, Aynan; Permana, Rian; Rizal, Syamsul; Purwinarti, Wiwin (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
Ari Gunadi, luthier from Rangkasbitung has been made classical guitar for years. He has problems, when he wants to make a good guitar, but only have cheap materials and tools. Ari realized that bracing is the most important part of the quality of a classical guitar. The aim of the study was to find out in detail about the organology of Ari Gunadi's bracing, and to find out the differences between Ari Gunadi's guitar bracing and similar bracing. The methodology used is descriptive qualitative by using observation, interviews, and literature as a medium for data collection. The research results obtained, that organologically Ari Gunadi used the "Fan Bracing" with using local hibiscus and mahogany wood, and using cheap tools. But, Ari Gunadi made changes to the shape of his guitar frame, such as the small frame on the top bracing wavy, and the large frame on the back bracing where the seat was curved. So when compared with fan bracing on other guitars, there are many differences that cannot be compared and becomes a unique characteristic of classical guitar bracing made by Ari Gunadi.